2017
DOI: 10.1097/nrl.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Delayed Initiation of Pharmacological Venous Thromboembolism Prophylaxis After an Intracranial Hemorrhage

Abstract: Initiation of early pharmacological prophylaxis in ICH patients did not appear to increase the risk of rebleeding nor decrease the risk of VTE. Among those patients who did develop VTE during hospitalization, there was a longer median time from admission to the first dose of pharmacological prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Although there is considerable apprehension about starting VTE prophylaxis after ICH, multiple trials have demonstrated that there is no increased risk of hematoma expansion when VTE prophylaxis is initiated within 48 hours [61][62][63]. Current guidelines recommend initiating mechanical VTE prophylaxis at the time of hospital admission and chemical VTE prophylaxis with unfractionated heparin or low-molecular-weight heparin within 1-4 days of admission in patients with stable hematomas and no evidence of ongoing coagulopathy, but preferentially within 48 hours (Table 8) [5,54]. Appropriately dosed for weight and organ function, VTE prophylaxis is recommended in all older adult patients unless a contraindication exists [64].…”
Section: Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%
“…Although there is considerable apprehension about starting VTE prophylaxis after ICH, multiple trials have demonstrated that there is no increased risk of hematoma expansion when VTE prophylaxis is initiated within 48 hours [61][62][63]. Current guidelines recommend initiating mechanical VTE prophylaxis at the time of hospital admission and chemical VTE prophylaxis with unfractionated heparin or low-molecular-weight heparin within 1-4 days of admission in patients with stable hematomas and no evidence of ongoing coagulopathy, but preferentially within 48 hours (Table 8) [5,54]. Appropriately dosed for weight and organ function, VTE prophylaxis is recommended in all older adult patients unless a contraindication exists [64].…”
Section: Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%
“…Venous thromboembolism is a common complication for patients suffering from a spontaneous intracerebral hemorrhage (ICH) [1,2]. The two primary methods of VTE prevention in use today are mechanical compression and pharmacological thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…While commonly used to prevent VTE in a variety of medical scenarios [11], the use of pharmacological thromboprophylaxis in ICH is an area of ongoing debate. The primary concern is that these medications may exacerbate intracranial bleeding but this has not been demonstrated in observational studies [1,12].…”
Section: Introductionmentioning
confidence: 99%
“… 2 To further complicate matters, patients with intracerebral haemorrhage are at an increased risk of venous thromboembolism (VTE). 3 The rates of symptomatic deep vein thrombosis (DVT) in intracerebral haemorrhage varies from 3% to 7%, and subclinical thrombotic events are reported to be as high as 17%. 4 5 The prophylactic prevention of this disorder is critical in preventing worsened outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Although trial data are limited, observational data have not shown an increased risk in haematoma expansion with the use of pharmacological antithrombotics. 3 8 Regardless, the concerns of haematoma expansion have contributed to the infrequent use of these agents in clinical practice. 9 …”
Section: Introductionmentioning
confidence: 99%